Value of Contrast-Enhanced Ultrasound in the Preoperative Evaluation of Papillary Thyroid Carcinoma Invasiveness - Chen, Lei; Chen, Luzeng; Liang, Zhenwei; Shao, Yuhong; Sun, Xiuming; Liu, Jinghua (Frontiers in Oncology, 2022)
Objective: To evaluate the diagnostic performance of preoperative contrast-enhanced ultrasound (CEUS) in the detection of extracapsular extension (ECE) and cervical lymph node metastasis (LNM) of papillary thyroid carcinoma (PTC), and the added value of CEUS in the evaluation of PTC invasiveness to conventional ultrasound (US). Materials and methods: 62 patients were enrolled retrospectively, including 30 patients with invasive PTCs (Group A, ECE or LNM present) and 32 patients with non-invasive PTCs (Group B). All patients underwent US and CEUS examinations before surgery. US and CEUS features of PTCs and lymph nodes were compared between groups. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and accuracy of US, CEUS and the combination of the two in the detection of ECE and LNM of PTC were calculated. Logistic regression was used to analyze relationships between variables. Results: The PTC size was larger in group A on both US and CEUS (P=0.001, P=0.003). More PTCs showed hyper-enhancement in group A (P=0.013) than in group B. More PTCs had >25% contact between PTC and the thyroid capsule and discontinued capsule on US and CEUS (all P<0.05) in group A than in group B. More absent hilum and, calcification, of lymph nodes were observed in group A (both P<0.05) than in group B on US. More centripetal perfusion and enlarged size of lymph nodes were observed in group A (bothall P<0.05) than in group B on CEUS. CEUS alone and US combined with CEUS manifested higher diagnostic accuracy (79.0%) than US alone (72.6%) in the detection of ECE. The combination of US and CEUS manifested the highest diagnostic accuracy (95.2%) than CEUS alone (90.3%) and US alone (82.2%) in the detection of LNM. Diagnosis of ECE and LNM by the combination of US and CEUS were independent risk factors of for PTC invasiveness (OR=29.49 and , 97.20, respectively; both P = 0.001). Conclusion: CEUS or US combined with CEUS is recommended for the detection of PTC ECE, while the combination of US and CEUS is most recommended for LNM detection. CEUS plays an essential role in the preoperative evaluation of PTC invasiveness.